Strategi Redaksi Indosport.com dalam Persaingan Industri Media di Era Digital - Fardani, Junita; Sumadiria, Haris; Imelda, Lida (Annaba: Jurnal Ilmu Jurnalistik, 2021)
This study aims to find out how Indosport.com's strategy is in managing the editorial system at the planning, organizing, implementing, and monitoring stages in industrial competition in the digital era. This study uses a qualitative approach with descriptive methods and George R. Terry's management theory. The results of this research are at the planning stage, Indosport.com forms media characteristics, improves SEO, builds relationships, collaborates, uses social media, maintains good relations with sources. The organizational structure is the same as other media, but uses a structural efficiency system. Ability and talent become benchmarks for classifying employees. The implementation stage is conducting editorial meetings, digital analysis via Google Trends, optimizing social media, and implementing the division of work shifts. At the monitoring stage, comparisons of projections with report results as well as evaluation of traffic data and provide warnings or sanctions if there are errors.